Understanding Employee Turnover Intention: The Effects of Work–Family Conflict, Job Stress, And Work–Life Balance - Najila Zasia Hasbullah; I Gusti Ayu Imbayani; Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to evaluate the effects of work-family conflict, work stress, and work-life balance on turnover intention among employees at the International Post Center (IPC) of PT Pos Indonesia (Persero) in Denpasar. High work pressure and demands have the potential to trigger role conflict, increase stress levels, and disrupt employees’ work-life balance, ultimately leading to a desire to quit. The research method used is quantitative, employing a survey approach. The population in this study includes all IPC employees at PT Pos Indonesia (Persero) in Denpasar, using a saturated sampling technique. Data were collected through questionnaire distribution and analyzed using multiple linear regression analysis. The study findings indicate that work-family conflict and work stress have a positive and significant impact on turnover intention. Conversely, work-life balance has a negative and significant impact on turnover intention. These findings indicate that the higher the level of work-family conflict and work-related stress, the higher the employees’ intention to leave the company. However, the better the work-life balance employees experience, the lower their intention to change jobs.